Using Stereoscopic 3D Images for Effective Learning in Primary School - Permana, Dede (Universitas Malikussaleh, 2019)
This study aims to determine the effect of using stereoscopic 3D image on learning effectiveness This research was conducted through a quasi-experiment in primary schools by using control class and experimental class. This research was joined by 52 participants (26 students in control class and 26 students in experimental class). The research conclusions indicate that, 1) stereoscopic 3D images can be used through integration into textbooks as illustrations increasing the primary school students perception about classroom activities (i.e., motivation, interest, challenge and excitement). and 2) textbooks integrated with stereoscopic 3D images are proven effective in improving the students' concept mastery, as seen from the independent sample t-test by using SPSS resulting in a probability (p) value of 0.000 with a significance level of 0.05 so that p < 0, 05.